2014
DOI: 10.1371/journal.pone.0101166
|View full text |Cite
|
Sign up to set email alerts
|

Lactic Acid and Thermal Treatments Trigger the Hydrolysis of Myo-Inositol Hexakisphosphate and Modify the Abundance of Lower Myo-Inositol Phosphates in Barley (Hordeum vulgare L.)

Abstract: Barley is an important source of dietary minerals, but it also contains myo-inositol hexakisphosphate (InsP6) that lowers their absorption. This study evaluated the effects of increasing concentrations (0.5, 1, and 5%, vol/vol) of lactic acid (LA), without or with an additional thermal treatment at 55°C (LA-H), on InsP6 hydrolysis, formation of lower phosphorylated myo-inositol phosphates, and changes in chemical composition of barley grain. Increasing LA concentrations and thermal treatment linearly reduced (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 55 publications
2
39
0
Order By: Relevance
“…These results also indicate that if P requirements of the rumen microbes are not met through readily available inorganic sources (diet or P recycled in saliva), rumen microbes may upregulate their endogenous phytase expression with CAc processing of barley. Another plausible reason may be that barley processing with CAc released P from InsP 6 as recently shown for LAc-treated barley (Metzler-Zebeli et al, 2014). Because nearly 61% of barley P (Metzler- Zebeli et al, 2014) and 50% of soybean meal P (Viveros et al, 2000), which were the major P sources in our basal diet, is InsP 6 , we assume that almost 2 g from the total 3.1 g of P/kg of DM of the native diet was InsP 6.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…These results also indicate that if P requirements of the rumen microbes are not met through readily available inorganic sources (diet or P recycled in saliva), rumen microbes may upregulate their endogenous phytase expression with CAc processing of barley. Another plausible reason may be that barley processing with CAc released P from InsP 6 as recently shown for LAc-treated barley (Metzler-Zebeli et al, 2014). Because nearly 61% of barley P (Metzler- Zebeli et al, 2014) and 50% of soybean meal P (Viveros et al, 2000), which were the major P sources in our basal diet, is InsP 6 , we assume that almost 2 g from the total 3.1 g of P/kg of DM of the native diet was InsP 6.…”
Section: Discussionmentioning
confidence: 94%
“…We recently showed that treating barley grain with organic acids modified the nutrient composition and enhanced the hydrolysis of InsP 6 Metzler-Zebeli et al, 2014;Harder et al, 2015a). This study aimed to evaluate the effects of barley grain treated with CAc and LAc on the abundance of welldescribed ruminal microbial populations, their microbial fermentation patterns, and nutrient degradation in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations